2018
DOI: 10.1080/17441692.2018.1516228
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review on community mobilisation for maternal and child health in sub-Saharan Africa: Impact on empowerment

Abstract: This review integrates evidence on community mobilisation (CM) for maternal and child health in sub-Saharan Africa (SSA) to identify the impact on empowerment. For the purposes of this review we use the following definition of CM: 'a capacity-building process through which community members, groups or organizations plan, carry out and evaluate activities on a participatory and sustained basis to improve their health and other conditions, either on their own initiative or stimulated by others', [Howard-Grabman,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…This might include developing a Community Advisory Board, seeking support from Chiefs and leaders in the community, and working with the government to influence policy [32]. Past research in the maternal health arena has successfully utilized community mobilization principles to create interventions within communities that are acceptable, sustainable, and impact health outcomes [34,35]. This type of community buy-in and support at the local and national level is necessary to overcome victim-blaming and structural barriers that impede access to post-assault services.…”
Section: Discussionmentioning
confidence: 99%
“…This might include developing a Community Advisory Board, seeking support from Chiefs and leaders in the community, and working with the government to influence policy [32]. Past research in the maternal health arena has successfully utilized community mobilization principles to create interventions within communities that are acceptable, sustainable, and impact health outcomes [34,35]. This type of community buy-in and support at the local and national level is necessary to overcome victim-blaming and structural barriers that impede access to post-assault services.…”
Section: Discussionmentioning
confidence: 99%
“…There are several well-conducted reviews of community engagement, mobilisation, and participation, as well as human rights-based approaches to RMNCAH, which have significant overlap with accountability approaches [43][44][45][46][60][61][62]. Similarly, findings on accountability initiatives from outside the RMNCAH field can enhance our understanding of effective approaches that could be applied to RMNCAH [23,[29][30][31]33,36,[63][64][65][66][67][68]. In particular, lessons could be drawn on the conceptualisation and measurement of "empowerment," which though often listed as an individual or collective outcome of social accountability approaches, appears to be infrequently operationalized, and poorly described in existing research [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Although women are generally satisfied with their care, many studies have identified barriers such as disrespect, neglect, abuse (often, verbal abuse), 12 , 20 - 23 and women’s limited decision-making power. 18 , 24 - 27 Few studies have explored women’s experiences in the context of childbirth in primary healthcare facilities, and women’s descriptions of their experiences after using delivery ward services are even scarcer. This study aims to learn about women’s birthing experiences and their thoughts about important aspects of delivery care in professionally staffed healthcare facilities.…”
Section: Introductionmentioning
confidence: 99%